1980
DOI: 10.1111/j.1365-246x.1980.tb04866.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat refraction and heat production in and around granite plutons in north-east England

Abstract: The country has both salt springs and hot springs, and the waters flowing from them provide hot baths, in which the people bathe separately according to age and sex. As Saint Basil says: "Water receives heat when it flows over certain metals,and becomes hot, and even scalding".'Bede, A History of the English a u r c h and People, 7 3 1. SummaryExisting surface heat flow determinations in north-east England indicate a difference in thermal structure between the Alston block of the North Pennines and the coastal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 28 publications
(32 reference statements)
2
48
0
Order By: Relevance
“…Hitherto, the definitive analysis of the geothermics of this borehole is again arguably that by England et al (1980). They determined that the best estimate of the heat flow came from the deeper part of the borehole within the Wensleydale granite, but did not specify the depth range of measurement.…”
Section: Raydalementioning
confidence: 96%
See 1 more Smart Citation
“…Hitherto, the definitive analysis of the geothermics of this borehole is again arguably that by England et al (1980). They determined that the best estimate of the heat flow came from the deeper part of the borehole within the Wensleydale granite, but did not specify the depth range of measurement.…”
Section: Raydalementioning
confidence: 96%
“…The Rookhope borehole (at NY 938 428) was the first to penetrate the Palaeozoic Weardale Granite that underlies most of County Durham in northeast England; the heat flow in this borehole has been extensively studied (e.g., Bott et al, 1972;England et al, 1980). Hitherto, the definitive analysis of the geothermics of this borehole is arguably that by England et al (1980).…”
Section: Rookhopementioning
confidence: 99%
“…It is commonly assumed that the most significant heat transfer occurs in a vertical direction, justified in the absence of rapid horizontal fluid flow (Bethke 1985;D e Bredhoeft, Djevanshir & Belitz 1988) or major lateral discontinuities in thermal properties (England, Oxburgh & Richardson 1980). Additional assumptions are that a steady state approximation is appropriate and that heat flow is independent of depth.…”
Section: Calculating the Thermal History In A Sedimentary Basinmentioning
confidence: 99%
“…England, Oxburgh & Richardson (1980) have recently questioned the validity of this assumption. Most studies available on the subject of lateral heat transport deal with the effects of thermal conductivity contrasts (Lachenbruch & Marshall 1966;Lee & Henyey 1974;Lee 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Simmons (1 967) calculated the heat flow anomalies created by bodies of different sizes and shapes. England et al (1980) carried out an extensive study of the effects of both conductivity and radioactivity contrasts for an isolated pluton, and found that the latter act to reduce depth-scale D. Both papers are confined to the case of an isolated body with uniform heat production, whereas the distribution of radioactivity is typically more complex.…”
Section: Introductionmentioning
confidence: 99%